EXPLORING STAIN PEKALONGAN STUDENTS’ STRATEGIES IN LEARNING ENGLISH LANGUAGE - Tuti Hastuti (Jurnal Penelitian Humaniora, 2014)
This study explored college students’strategies in learning English language. Two questions were presented. The first question is what strategies are used by the students in learning English language and the second question is how do the students use strategies in learning English language. To answer the first question, 49 college students gave respond on Strategy Inventory for Language Learning (SILL) questionnaire. Then, to answer the last question, five students participated in Think Aloud Protocol (TAP) sessions. The data analysis from SILL questionnaire showed that the students were medium user of strategies in learning English language. The strategies then ranked from social strategies, followed by metacognitive, cognitive, affective, compensation, and memory strategies at the latter posi- tion. Then, to find out how the students use strategies in learning English language, think aloud protocol (TAP) sessions presented that the students made use of three major strategies in learning English language cognitive strategies, metacognitive strategies, and compensation strategies. These three strategies were used by the students in three different activities (understanding reading passage, dealing with unfamiliar words or phrases and self-awareness) as the study was limited to reading skills. In conclusion, the students made use of different strategies when doing particular task given to them. At this point, students in some ways have the ability to learn by themselves, that is by using strategies as lecturers cannot always facilitate students’ learning, especially when lecturers teach large classes.